Does Macroeconomic Moderate The Effect of Risk and Diversification on Financial Stability? Evidence from Islamic Commercial Bank - Humanita, Salwa Nabella Aksi; Haryono, Slamet; Putri, Amila Zamzabila (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2024)
Islamic banking's financial stability can improve efficiency and health and be able to withstand shocks originating from internal and external factors. This study analyzes the impact of risk, diversification, and inflation on the financial stability of Islamic banking. By using monthly time series data from 2018–2022, the analysis method used is multiple linear regression and moderate regression analysis (MRA) using the Eviews version 10 application. The results showed that the credit risk variable (NPF) has a significant negative relationship to financial stability (Z-Score). As well as the liquidity risk variable (FDR), financing diversification has a significant positive effect on the financial stability of Islamic banking (Z-Score). Macroeconomic variables (inflation) can strengthen the effect of financing diversification and weaken the effect of liquidity risk (FDR), but inflation cannot moderate the effect of credit risk (NPF) on the financial stability of Islamic banking (Z-Score). This study introduces a new theoretical approach to the conceptual relationship between variables. The findings can serve as a reference for monetary authorities in considering the impact of inflation in setting financial stability policies.